2009
DOI: 10.1152/ajpcell.00129.2009
|View full text |Cite
|
Sign up to set email alerts
|

Epac increases melanoma cell migration by a heparan sulfate-related mechanism

Abstract: 2009.-Melanoma, the most malignant form of human skin cancer, has a poor prognosis due to its strong metastatic ability. It was recently demonstrated that Epac, an effector molecule of cAMP, is involved in regulating cell migration; however, the role of Epac in melanoma cell migration remains unclear. We thus examined whether Epac regulates cell migration and metastasis of melanoma. Epac activation, by either specific agonist or overexpression of Epac, increased melanoma cell migration. Deletion of endogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 47 publications
1
59
0
Order By: Relevance
“…These results suggest that Ca 2+ -dependent cell migration occurs first, followed by heparan sulfate-related cell migration. Regarding the status of Epac activation, our data suggest that the heparan sulfate-related mechanism is involved in both basal and Epac-activated conditions (9), but the Ca 2+ -dependent mechanism participates only in an Epac-activated condition. Melanoma cell migration was reduced under both basal and Epac-activated conditions with inhibition of molecules involved in the heparan sulfate-related mechanism (9).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…These results suggest that Ca 2+ -dependent cell migration occurs first, followed by heparan sulfate-related cell migration. Regarding the status of Epac activation, our data suggest that the heparan sulfate-related mechanism is involved in both basal and Epac-activated conditions (9), but the Ca 2+ -dependent mechanism participates only in an Epac-activated condition. Melanoma cell migration was reduced under both basal and Epac-activated conditions with inhibition of molecules involved in the heparan sulfate-related mechanism (9).…”
Section: Discussionmentioning
confidence: 77%
“…Because Epac1 expression was higher in SK-Mel-187 than in SK-Mel-2, these data suggest that Epac1 expression positively correlates, at least in part, with Rap1 activation, and the resultant Ca 2+ elevation in melanoma. We previously reported that heparan sulfate is involved in Epac-induced melanoma cell migration (9). Using SK-Mel-2 cells, we showed that Epac mediates cell migration via increased heparan sulfate production.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations